2009
DOI: 10.1007/s11999-008-0341-1
|View full text |Cite
|
Sign up to set email alerts
|

Which Regions of the Operating Gown Should be Considered Most Sterile?

Abstract: Various guidelines have been proposed regarding which portions of a surgical gown may be considered sterile. Unfortunately, the validity of these recommendations has not been definitively established. We therefore evaluated gown sterility after major spinal surgery to assess the legitimacy of these guidelines. We used sterile culture swabs to obtain samples of gown fronts at 6-inch increments and at the elbow creases of 50 gowns at the end of 29 spinal operations. Another 50 gowns were swabbed immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…9 The tips of sterile culture swabs (StarSwab IITM with liquid Stuart's medium; Starplex Scientific Inc, Etobicoke, Ontario, Canada) initially were dipped in sterile saline to facilitate extraction of any contaminants present on the thyroid shields surface. The swabs were shaken gently to remove any excess fluid before being used to sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The tips of sterile culture swabs (StarSwab IITM with liquid Stuart's medium; Starplex Scientific Inc, Etobicoke, Ontario, Canada) initially were dipped in sterile saline to facilitate extraction of any contaminants present on the thyroid shields surface. The swabs were shaken gently to remove any excess fluid before being used to sample.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7] Disposable gowns designated as being "impervious" have also been shown to have weaknesses when exposed for prolonged periods or in areas where panels are joined together. 8,9 The most common organisms identified in orthopedic infections are coagulase negative staphylococcus species like Staphylococcus epidermidis and the coagulase positive Staphylococcus aureus. 10,11 Many orthopedic cases including spine surgery, trauma surgery, and elective limb realignment surgery are using intraoperative fluoroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, there are reports that there is considerable variability among some interventionalists with regard to the level of aseptic precautions that are taken. In a United Kingdom survey of 100 orthopedists, 100 rheumatologists, and 50 general practitioners, Charalambous et al found that less than 50% of the respondents routinely wore gloves and even fewer (16.8%) used sterile towels to isolate the sterile field when performing ultrasound-guided knee injections.…”
Section: Infectionmentioning
confidence: 99%
“…Bible et al recently determined that despite proper use of surgical gown and sterile technique, all 50 gowns tested after spinal operations were contaminated with bacteria. The least contaminated areas were between the chest and the level of the surgical fi eld, whereas the most contaminated were the areas below the waist, the neck, and the elbow creases (Bible et al 2009 ).…”
Section: Body Exhaust Suitsmentioning
confidence: 99%